Grading zero waste design using digital and virtual methods - Ejeimi, Sahar Hassan (Kansas State University, 2020)
Traditional practices of pattern cutting within the apparel industry result in a considerable portion of fabric waste that negatively impacts the environment. Currently, garment manufacturers make responding to fashion trends, at the lowest possible cost, the main priority, regardless of fabric waste, to ensure economic profit. Besides, one of the sustainable challenges when working with zero waste design (ZWD) is the feasibility of pattern grading under the current apparel production system. Thus, the purpose of this experimental study was to explore the feasibility of grading zero waste garments for industry production using digital and virtual methods. The main research questions in this study were: What pattern piece adjustments and marker layouts achieve both 100% marker efficiency and accurate virtual visual appearance? Can digital 3D simulation be used as an effective and sustainable sizing and fit assessment tool? Does attachment and appreciation of ZWD influence expert judges’ evaluation of visual accuracy? The first research question was answered through a functional design process that included three phases: sample development, grading and marker making, digital and virtual testing of marker adjustments, and marker refinement. The application of typical and novel marker making and design tactics for functional utilization of the cuts offs resulting in no fabric waste of the mixed marker of the graded sizes was explored. As a result, a system of four different adjustment methods were applied to reach 100% marker efficiency while maintaining visual accuracy. Multiple challenges regarding the use of 3D simulation to create virtual samples were encountered. To answer the second and third research questions, an online questionnaire was utilized to collect assessment related to the efficiency of the graded virtual samples compared to the physical based on particular design criteria. Two judge groups participated in this study, zero waste design academic researchers and industry technical designers. The judges compared the samples via video, between and across groups. The findings indicated that the use of 3D simulation was mostly challenging for grading ZWD while maintaining 100% marker efficiency and visual accuracy. Judges suggested that the 3D simulation would be a useful, sustainable tool for fit and appearance assessment to decrease the number of physical samples; however, major improvements for the software were recommended before the physical sample could be eliminated. These findings contribute to understanding the effectiveness of sizing zero waste design and use of 3D virtual simulation as an assessment method, which promotes sustainable development through pattern making within the production methods in the apparel industry. Technical judges had more agreement than ZWD judges regarding the similarity between virtual and physical samples, and the sufficiency of information provision by virtual samples that would replace physical samples. Thus, ZWD judges had higher expectations for virtual technology. This finding indicated a relationship between attachment and appreciation of sustainability in fashion with the adoption of advanced practices to develop sustainable fashion design through the functional design process.
Keywords: zero waste design; apparel grading; 3D simulation; marker making